Implementasi Peraturan Bupati Kabupaten Bandung No.78 Tahun 2021 Tentang Program Sekolah Mengaji dan Dampaknya Terhadap Kemampuan Membaca Al-Qur’an Siswa SMPN 2 Rancaekek - Isma Ruliyanti; Eko Surbiantoro (Bandung Conference Series: Islamic Education, 2024)
Abstract. The program is about learning to read, write, and memorize the Qur'an. The researcher chose to study at SMPN 2 Rancaekek because the school has been implementing the Koranic school program for 2 years. This research aims to: (1) Examine the background of the birth of Bandung regent regulation number 78 of 2021 concerning the school recitation program. (2) Identify the implementation of Bandung regent regulation number 78 of 2021 concerning the school recitation program at SMPN 2 Rancaekek. (3) Analyzing the effect of the implementation of the Bandung Regency Regent Regulation number 78 of 2021 concerning the Koranic School program on the ability to read the Qur'an. (4) Finding the supporting and inhibiting factors of the Bandung Regency Regent Regulation number 78 of 2021 concerning the Koranic School program. This researcher used a mixed method research approach with a sequential mixed method research method using data collection techniques using documentation, observation, interviews, and tests. As for data analysis, researchers used validity tests, reliability tests, normalization tests, homogeneity tests, and t tests. Furthermore, for data collection techniques, researchers used the Al-Qur'an and Iqra reading ability tests with a total of 4 questions. Abstrak. Peneliti memilih penelitian di SMPN 2 Rancaekek dikarenakan sekolah tersebut sudah melaksanakan program sekolah mengaji selama 2 tahun. Penelitian ini bertujuan untuk: (1) Mengkaji latar belakang lahirnya peraturan bupati kabupaten Bandung Nomor 78 tahun 2021 tentang program sekolah mengaji. (2) Mengidentifikasi implementasi Peraturan Bupati Kabupaten Bandung nomor 78 tahun 2021 tentang program sekolah mengaji di SMPN 2 Rancaekek. (3) Menganalisis pengaruh implementasi Peraturan Bupati Kabupaten Bandung nomor 78 tahun 2021 tentang program Sekolah Mengaji terhadap kemampuan membaca Al-Qur'an. (4) Menemukan faktor pendukung dan penghambat Peraturan Bupati Kabupaten Bandung nomor 78 tahun 2021 tentang program Sekolah Mengaji. Peneliti ini menggunakan pendekatan penelitian mixed metode dengan metode penelitian mixed metode sequential teknik pengumpulan data peneliti menggunakan dokumentasi, observasi, wawancara, dan tes. Adapun analisis data peneliti menggunakan uji validitas, uji reliabilitas, uji normalisasi, uji homogenitas, dan uji t. Selanjutnya untuk teknik pengumpulan data peneliti menggunakan tes kemampuan membaca Al-Qur'an dan Iqra dengan jumlah 4 butir soal .